SOCIO-ECONOMIC ANALYSIS OF THE QUALITY OF LIFE OF THE ROMANI POPULATION IN THE REGION OF THE AUTONOMOUS PROVINCE OF VOJVODINA - Jovanović, Jelena; Nikolić, Ivica; Petković, Violeta (Poslovna ekonomija, 2023)
The subject of this paper is a social economic analysis of the quality of life of the Romani population in the region of the Autonomous Province of Vojvodina. Life on the ‘edge of poverty’, often endangering basic human needs and postulates worthy of a man of the 21st century, represents an imperative to a wide social community to include all its resources, so that the Roma have a dignified life and an equal status with other members of society. Seen from a sociological aspect, the concept of quality of life provides information on satisfaction with one’s life and the degree of adequate functioning in the environment. In a theoretical sense, the position of each individual in society is influenced by some factors, which also apply to the Romani population. In order to establish someone’s position in society, it is necessary to define criteria, which can be also called influencing factors. During the research, the principles of PEST analysis were used, with predefined political, economic, sociological-cultural, and technological criteria, i.e. factors, based on which the current position of the Roma was tested, and, the hypothetical ones, were projected on the quality of their life in the future. The general goal of this research is to improve the position of the Romani community in AP Vojvodina, observed from the point of view of the economic and social status that affects the quality of life (subjective and objective factors and others). The specific goal of the research presented in the paper is the valuation of subjective and objective factors and their direct influence on the quality of the lives of Roma. The research sample population is represented by members of the Romani community who live in the territory of AP Vojvodina.